Marine Energy Turbine Performance: Effect of Blade Sweep. (December 2016) - Halder, Paresh; Samad, Abdus
Abstract: The present paper investigates blade sweep effect of a Wells turbine used in an oscillating water column (OWC) to extract wave energy. The numerical analysis of flow was carried out by using a commercial software ANSYS CFX® v14. 0. Two different blades were used: unswept blade and 10 o backward-swept blade, respectively. It was found that the backward swept blade strongly affects the blade stall margin. It was also observed that the flow separations of the swept and unswept blades occur near the trailing edge and the leading edge, respectively.